Documenting the challenges of the late antique Miaphysite church - Blaudeau, Philippe; Nuffelen, Peter van (Texts and studies in Eastern Christianity, 2026)
"The earliest history of the miaphysite church is extraordinarily rich in documents. This volume asks why and how the Miaphysite Church produced such an extraordinary theological, canonical and historical documentation? In order to make these collections more accessible for future historians, contributors study the make-up of the collections, the images that they project, their transmission and translation, and what kind of information they provide for modern historians"-- Provided by publisher